Contribution of transverse bulkheads to hull stiffness of large container ships - Senjanović, Ivo (Array, 2008)
Summary: Ultra large container ships are rather fl exible and exposed to signifi cant wave deformations. Therefore, the hydroelastic strength analysis is required for these types of ships. The coupling of a beam structural model and a 3D hydrodynamic model is preferable for reasons of simplicity. In this paper, the contribution of large number of transverse bulkheads to general hull stiffness is analysed. The prismatic pontoon with the cross-section of a large container vessel is considered for this purpose. The 3D FEM torsional analysis is performed with transverse bulkheads included and excluded. The correlation analysis of the obtained deformations indicated the infl uence of transverse bulkheads on the ship hull stiffness. The analysis is done by employing the torsional theory of thin-walled girders